2012
DOI: 10.1007/s00256-012-1551-x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging frequently changes classification of acute traumatic thoracolumbar spine injuries

Abstract: Objective To evaluate the influence of additional (MRI) compared with computed tomography (CT) alone for the classification of traumatic spinal injuries using the Arbeitsgemeinshaft für Osteosynthesefragen (AO) system and the ThoracoLumbar Injury Classification and Severity (TLICS) scale. Materials and methods Images from 100 consecutive patients with at least one fracture on CT were evaluated retrospectively by three radiologists with regard to the AO and TLICS classification systems in 2 steps. First, all im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 30 publications
0
52
0
Order By: Relevance
“…The authors suggested that Magnetic Resonance Imaging (MRI) could be used for further investigation of ligamentous injuries and was found to be helpful in some cases. 18 In our study, 64.8% of the patients had total reproducibility between the newly AO spine groups (A, B and C), whereas only 55.2% had perfect concordance regards to sub-type classification. The Kappa index for major groups, A, B and C, was respectively 0.75 (good), 0.7 (good) and 0.85 (almost perfect).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The authors suggested that Magnetic Resonance Imaging (MRI) could be used for further investigation of ligamentous injuries and was found to be helpful in some cases. 18 In our study, 64.8% of the patients had total reproducibility between the newly AO spine groups (A, B and C), whereas only 55.2% had perfect concordance regards to sub-type classification. The Kappa index for major groups, A, B and C, was respectively 0.75 (good), 0.7 (good) and 0.85 (almost perfect).…”
Section: Discussionmentioning
confidence: 90%
“…For example, the controversial evaluation of the status of the Posterior Ligament Complex (PLC), are instead integrated into the A, B and C classification and potentially minimize inter-observer disagreement. 11,16,18 Moreover, it was designed primarily as a Computer Tomography (CT) classification, as these are widely available imaging modalities in trauma centers around the world. The authors suggested that Magnetic Resonance Imaging (MRI) could be used for further investigation of ligamentous injuries and was found to be helpful in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of PLC is important because its failure significantly influences the severity of the fracture (52). In a recent study MRI increased the severity of CT score of TL fractures in 31% of patients and in 22% changed the indication for conservative treatment (score <5 points) to indication for surgery (score ≥5 points) (53).…”
Section: Classification Systemsmentioning
confidence: 99%
“…The lack of anterior support was also evaluated by the system proposed by McCormack et al (12,13), grading the degree of vertebral bone injury according to Copyright In the last decades, other CT scan-based characteristics were associated with more severe burst fractures and potential injury of the posterior ligamentous complex, labeling such injuries according to some authors as "unstable" burst fractures. These characteristics are facet joint diastasis, splaying of the spinous process and minor dislocations (8,14,15). Although all these radiological features are potentially associated with a worse outcome, the evidences that indicate surgery are generally weak.…”
mentioning
confidence: 99%
“…Magnetic resonance imaging may show signs of severe injuries that would be underestimated in some cases using plain radiographs or CT scan. However, MRI changes must be interpreted together with CT scan, once its use isolated may lead to unnecessary surgeries (1,4,9,14,17,19).…”
mentioning
confidence: 99%